Efeito do extrato de própolis sobre o desempenho, a hematologia, sistema imune e morfologia intestinal do pacu (Piaractus mesopotamicus) - Muzzolon, Angelita (2018)
Intensive aquaculture systems increase susceptibility to disease, due to stress conditions, negatively influencing fish immune systems. Therefore, there is a need to adopt good cultivation practices, reducing chemotherapeutic applications and favoring the use of immunostimulating substances, such as propolis. The aim of the present study was to determine the effect of diets supplemented with ethanolic propolis extracts (EPE) on pacu performance, hematological, immunological, morphological and body composition. Pacu juveniles with mean weight of 200.8 ± 44.6 g were randomly distributed in four boxes (250 L, ten fish per box) and fed for 60 days with a diet containing EPE (0.0, 1.5, 3.0, 4.5%) in a completely randomized design (n = 10). At the end of the experimental period, fish fed 1.5% EPE presented higher (P <0.05) weight gain and specific growth rate, lower (P <0.05) feed conversion and higher (P <0.05) thickness of the intestinal muscle layer. The addition of dietary EPE also conferred higher (p<0.05) Burst leukocyte respiratory activity, as well as higher moisture and body lipid levels when compared to the control treatment. The use of EPE in pacu feeding was effective as a growth promoter and immunostimulant.